Upaya Meningkatkan Kinerja Guru dalam Melaksanakan Model Pembelajaran Kooperatif melalui Supervisi Akademik di SDN 4 Sikur Kecamatan Sikur Tahun Pelajaran 2020/2021 - Kartiwi, Kartiwi (Lembaga Yasin AlSys, 2021)
This research is a school action research (PTS) which raises about how teachers can use problem-based cooperative learning models in the learning process in the classroom with the intention of increasing their performance in learning carried out in class and the evaluation is carried out through continuous mentoring activities of the principal. This school action research activity was carried out at SDN 4 Sikur for 3 months, starting from January to March 2021 by going through cycle stages. The purpose of this school action research (PTS) is to find out the extent to which continuous mentoring carried out by school principals followed by the provision of guidance/treatment to target teachers can improve the competence of these teachers in classroom learning. In this school action research (PTS) it was carried out in 2 cycles, from the results of the actions taken it was proven to be able to improve teacher performance by achieving ideal standards. In the first cycle the increase in teacher competence after classroom supervision after continuous coaching has only reached about 66.67% in the second cycle it can increase to 100%. The average score obtained after class supervision in the first cycle was 63.30 and increased in the second cycle to 83.33, meaning that there was an increase of 20.03 and the level of completeness as a group/classical in the first cycle reached 66.67% and in the second cycle increased to 100%. The results of this school action research show that coaching/assistance in the academic supervision of the principal can improve teacher performance in utilizing the problem-based cooperative learning model.